Islam in Britain, 1558-1685 - Matar, N. (Cambridge University Press, 1998)
This book examines the impact of Islam on Britain between 1558 and 1685. Professor Matar provides a perspective on the transformation of British thought and society by demonstrating how influential Islam was in the formation of early modern British culture. Christian-Muslim interaction was not, as is often thought, primarily adversarial; rather, there was extensive cultural, intellectual and missionary engagement with Islam in Britain. The author documents conversion both to and from Islam, and surveys reactions to these conversions. He examines the impact of the Qur'an and Sufism, not to mention coffee, on British culture, and cites extensive interaction of Britons with Islam through travel, in London coffee houses, in church, among converts to and from Islam, in sermons and in plays. Finally, he focuses on the theological portrait of Muslims in conversionist and eschatological writings.